Pengaruh Kepemilikan Institusional, Leverage, dan Likuiditas Terhadap Financial Distress - Shanaz Anggita Utari; Sri Trisnaningsih (Al-Buhuts, 2024)
The purpose of this research was to look at how liquidity, leverage, and institutional ownership affect financial hardship. This study employed earnings per share (EPS) as its financial distress metric. This study's population included companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022 that were involved in the property and real estate sectors. This study used secondary data as its basis and was quantitative in nature. Financial distress served as the dependent variable in this study, with institutional ownership, leverage, and liquidity serving as the independent variables. The study's population consisted of 78 different businesses. For the years 2020–2022, this study collected 72 observational data points from a purposive sample of 24 different organizations. For the analysis, the researchers used the statistical program SPSS, version 26. The study's findings indicate that institutional ownership significantly exacerbated financial distress, while leverage and liquidity had no effect.